The Essence of The Distance Education Method in Foreign Language Lessons - Jurayeva Shalolakhan Khusanboyevna (Genius Publishing Group, 2023)
This article provides feedback on the educational process and its effective methods, the essence of distance education
Keywords: Education; student; online; technology